Ukraine as a field of conflict of linguistic and ethnic identities with didactic suggestions for German as a foreign or second language (DaF/DaZ) (Educational Dimension, 2025)
In the first part of our contribution we present a brief overview of the history of Ukraine with a focus on national identity and the founding myth of Vladimir (claimed by Ukrainians and Russians) as well as a history of the Ukrainian and the Russian language in the territory of Ukraine. The second part consists of a mixed methods (quantitative and qualitative) analysis of the answers to a questionnaire sent online to Ukrainians and answered by 160 respondents in 2023. The key complex are the questions concerning the use of Ukrainian and Russian as perceived by the Ukrainian population and the attitudes towards these two languages after the beginning of the war in 2023. In the third part we present didactic suggestions for classes in German as a foreign or second language on the basis of the answers to our questionnaire and a text on Wladimir/Volodymir. The tasks use ChatGPT, Google Forms, Mentimeter, LearningApps and Zumpad for the exercises.
Keywords: Ukraine; Ukrainian language; national identity of Ukraine; founding myth; didactic suggestions; German as a foreign / second language